2021
DOI: 10.1371/journal.pone.0246474
|View full text |Cite
|
Sign up to set email alerts
|

Sex and gender differences in presentation, treatment and outcomes in acute coronary syndrome, a 10 year study from a multi-ethnic Asian population: The Malaysian National Cardiovascular Disease Database—Acute Coronary Syndrome (NCVD-ACS) registry

Abstract: Background Sex and gender differences in acute coronary syndrome (ACS) have been well studied in the western population. However, limited studies have examined the trends of these differences in a multi-ethnic Asian population. Objectives To study the trends in sex and gender differences in ACS using the Malaysian NCVD-ACS Registry. Methods Data from 24 hospitals involving 35,232 ACS patients (79.44% men and 20.56% women) from 1st. Jan 2012 to 31st. Dec 2016 were analysed. Data were collected on demographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 53 publications
1
21
0
2
Order By: Relevance
“…The women in the study group were older and more often had diabetes, hypertension, heart failure, and renal failure than the men. Among the women, there was a higher rate of in-hospital, 30-day, and annual mortality in both the STEMI and NSTEMI groups [ 23 ]. Women have a higher risk for thrombotic and bleeding events compared to men.…”
Section: Discussionmentioning
confidence: 99%
“…The women in the study group were older and more often had diabetes, hypertension, heart failure, and renal failure than the men. Among the women, there was a higher rate of in-hospital, 30-day, and annual mortality in both the STEMI and NSTEMI groups [ 23 ]. Women have a higher risk for thrombotic and bleeding events compared to men.…”
Section: Discussionmentioning
confidence: 99%
“…Variations of in-hospital management for different groups of interest according to demographics, risk factors and co-morbidities were analysed using multivariate logistic regression, presented as adjusted odds ratio (aOR) with a 95% confidence interval (CI). The choice of covariates was based on factors influencing ACS management in the literature and included gender, ethnicity, types of ACS, risk factors and co-morbidities [ 22 ]. A probability ( p ) value of less than 0.05 is considered statistically significant.…”
Section: Methodsmentioning
confidence: 99%
“…7 The few studies that looked into gender differences among ACS patients showed that women had an atypical presentation and that they often took longer to seek medical care, both of which act as contributory factors in delaying appropriate management. 8 Qinghua et al reported a higher incidence of unstable angina and thrombolysis in myocardial infarction (TIMI) III flow in women but with a higher mortality both inhospital and in the long-term follow-up. 9 The Gulf RACE-I study, which was conducted in 2007, including six Middle Eastern countries, showed that mortality among women with ACS was higher than among men.…”
Section: Introductionmentioning
confidence: 99%